13
$\begingroup$

Question: For positive real numbers $a,b,c$ and $d$, find the smallest possible value of the following expression: $$\large{\left \lfloor{\frac{b+c+d}{a}} \right \rfloor+ \left \lfloor{\frac{a+c+d}{b}} \right \rfloor+\left \lfloor{\frac{a+b+d}{c}} \right \rfloor+\left \lfloor{\frac{a+b+c}{d}} \right \rfloor}$$


Note: For this question, the expression $\lfloor x \rfloor $ stands for the greatest integer function of x. For example, $\lfloor 2.5 \rfloor=2$, while $\lfloor -2.5 \rfloor=-3$

Bonus: Generalise the problem to $n$ numbers $a_1,a_2,\ldots,a_n$.

$\endgroup$
16
$\begingroup$

We use the following two tools:

  • Tool 1: Every real number $x$ satisfies $\lfloor x\rfloor>x-1$ (with strict inequality).
  • Tool 2: All positive real numbers $y$ and $z$ satisfy $\frac{x}{y}+\frac{y}{x}\ge2$; indeed this inequality is equivalent to $y^2+z^2\ge2yz$ and $(y-z)^2\ge0$.

Now the expression $E$ that is to be minimized can be estimated (by using these two tools) as follows: \begin{eqnarray*} E &=& \left\lfloor\frac{b+c+d}{a} \right\rfloor+ \left\lfloor\frac{a+c+d}{b} \right\rfloor+ \left\lfloor\frac{a+b+d}{c} \right\rfloor+ \left\lfloor\frac{a+b+c}{d} \right\rfloor \\ &>& \left(\frac{b+c+d}{a}-1\right)+ \left(\frac{a+c+d}{b}-1\right) + \left(\frac{a+b+d}{c}-1\right) + \left(\frac{a+b+c}{d}-1\right) \\ &=& \left(\frac{a}{b}+\frac{b}{a}\right)+ \left(\frac{a}{c}+\frac{c}{a}\right)+ \left(\frac{a}{d}+\frac{d}{a}\right)+ \left(\frac{b}{c}+\frac{c}{b}\right)+ \left(\frac{b}{d}+\frac{d}{b}\right)+ \left(\frac{c}{d}+\frac{d}{c}\right) -4 \\ &\ge& ~6\cdot2-4 ~~=~~ 8. \end{eqnarray*} We get $E>8$. Since $E$ is the sum of four integers and hence integer itself, this actually implies the lower bound $E\ge9$. Finally, for $a=4$ and $b=c=d=5$ the expression attains the value $9$.

Hence the smallest possible value of the above expression is

$~~~9~$ (nine)


For the Bonus question, the above argument easily generalizes. The resulting lower bound is $$ E ~>~ {n\choose 2}\cdot 2 -n, $$ which implies $E\ge(n-1)^2$. By setting $a_1=n$ and $a_2=a_3=\cdots=a_n=n+1$, we get $$\left\lfloor\frac{a_2+a_3+\cdots+a_n}{a_1} \right\rfloor = \left\lfloor\frac{(n-1)(n+1)}{n} \right\rfloor = \left\lfloor n-\frac{1}{n} \right\rfloor = n-1,$$ and $$\left\lfloor\frac{a_1+a_3+\cdots+a_n}{a_2} \right\rfloor = \left\lfloor\frac{(n-2)(n+1)+n}{n+1} \right\rfloor = \left\lfloor (n-2)+\frac{n}{n+1} \right\rfloor = n-2.$$ The resulting value of the expression is $(n-1)+(n-1)(n-2)=(n-1)^2$, and hence coincides with the lower bound.

Summarizing, the smallest possible value of the expression in the Bonus question

$~~~(n-1)^2$

$\endgroup$
  • $\begingroup$ That's it.You nailed it. $\endgroup$ – Dragonemperor42 Mar 19 '16 at 17:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.